Analisis Perlakuan Atas Selisih Kurs Dan Transaksi Mata Uang Asing Terhadap Laporan Keuangan Pada Pt. Indofood Sukses Makmur Tbk - Eka Febrianti; Makhrusatun Inka Widayani; Dewi Yuni Windarti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
. Accounting for exchange rate differences and foreign currency transactions has a significant impact on annual financial reports. Companies that trade foreign currencies must apply appropriate accounting policies to record exchange rate differences that occur. This research aims to analyze the accounting treatment of exchange rate differences and foreign currency transactions at PT. Indofood Sukses Makmur Tbk The method used in this research is a descriptive method using secondary data obtained from the company's financial reports. The research results are based on the application of PT. Indofood Sukses Makmur Tbk's accounting principles in accordance with Financial Accounting Standards (SAK). The author notes translation differences when recognizing income or expenses and does not consider translation differences when recording assets or liabilities. This research also shows that the resulting exchange rate differences have a significant impact on PT's annual financial reports. Indofood Sukses Makmur Tbk. A favorable exchange rate difference can increase the company's net profit, while an unfavorable exchange rate difference can reduce the company's net profit.